2014
DOI: 10.2174/1566524013666131118112431
|View full text |Cite
|
Sign up to set email alerts
|

Novel Adjunctive Therapies for the Treatment of Tuberculosis

Abstract: Despite significant efforts to control tuberculosis (TB), the disease remains a major global threat, with an estimated 8.6 million new cases and 1.3 million deaths in 2012 alone. Significant treatment challenges include HIV co-infection, the dramatic rise of multidrug-resistant TB and the vast reservoir of latently infected individuals, who will develop active disease years after the initial infection. The long duration of chemotherapy also remains a major barrier to effective large scale treatment of TB. Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 125 publications
0
17
0
Order By: Relevance
“…Additionally, in children, adjunctive corticosteroids have been shown to not only be beneficial in reducing mortality, but also in reducing neurologic sequelae (Girgis et al, 1991; Schoeman et al, 1997). However, corticosteroid use leads to a nonspecific modulation of the immune response with significant side effects that can limit its use (Ordonez et al, 2014). Therefore, there is an urgent need for the development and validation of novel host-directed therapies for CNS TB.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in children, adjunctive corticosteroids have been shown to not only be beneficial in reducing mortality, but also in reducing neurologic sequelae (Girgis et al, 1991; Schoeman et al, 1997). However, corticosteroid use leads to a nonspecific modulation of the immune response with significant side effects that can limit its use (Ordonez et al, 2014). Therefore, there is an urgent need for the development and validation of novel host-directed therapies for CNS TB.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that by reducing proinflammatory-cytokine production, roflumilast increases the proportion of rapidly dividing bacilli and thereby enhances isoniazid killing. While roflumilast had marginal effects on cellularity at early time points, adjunctive therapy with isoniazid certainly suggests that roflumilast may improve lung pathology at later time points and murine survival with adjunctive therapies and shorten the time to sterilization during multidrug TB treatment in the mouse model, as has been shown with other HDT agents (2,4). Since a high proportion of new drug candidates in development fail to advance to clinical use (16), the fact that roflumilast is already FDA approved makes it an attractive candidate for further evaluation.…”
mentioning
confidence: 98%
“…While type 4 PDE-I (PDE4-I) therapies have been hampered by adverse-effect profiles, two have been approved by the Food and Drug Administration (FDA) since 2011 and others are in development (3). PDE4-Is have recently been studied as adjunctive therapies for TB (1,4). Although the synergism of the PDE4-I CC-3052 with isoniazid (INH) has been reported (5), our group found that, when used as part of a complete tuberculosis multidrug regimen, the PDE4-I rolipram was detrimental to bacterial clearance (6).…”
mentioning
confidence: 99%
“…Host-directed therapies could potentially be used in synergy with optimised drug regimens to boost or protect the host tissues or cells. Therapies could include corticosteroids, TNF-α inhibitors, phosphodiesterase inhibitors and matrix-metalloproteinases (Ordonez et al, 2014), as well as infusion of autologous mesenchymal stromal cells (Skrahin et al, 2014). With recent advances in rapid molecular drug susceptibility testing (Xie et al, 2017) and judicious prescribing stewardship of the newly available drugs, including an all oral treatment regimen (WHO, 2018b) we anticipate a substantial impact on the treatment of MDR and XDR-TB as new recommendations emerge from ongoing clinical trials.…”
Section: Discussionmentioning
confidence: 99%